Rumah Haji Ismail, Kampung Parit Bengkok, Batu Pahat, Johor / [kad apertur] - Zulbahrin Abdul Ghafar; Rohana Mohd. Noor; Norain Mohd. Saad; Mazlan Abdullah; Abdul Aziz Mohamad (Kuala Lumpur : Universiti Teknologi Malaysia, 1981)
02